2008
DOI: 10.1007/s11274-008-9914-0
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of Cladosporium cladosporioides (Fresen.) de Vries in laboratory conditions, as a potential candidate for biocontrol of Tetranychus urticae Koch

Abstract: A survey for natural entomopathogenic fungi of two spotted spider mite (Tetranychus urticae) adults was made in Erzurum, Turkey, during the period 2006. Tetranychus urticae (65.8%) infected with a strain of the fungus Cladosporium cladosporioides were found. Thirteen isolates of C. cladosporioides were assessed against T. urticae, in a single dose (8 9 10 6 conidia ml -1 ), laboratory bioassay on bean leaflets. The total mortality percentage caused by C. cladosporioides isolates varied from 50.95 to 74.76% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Cladosposrium sp. has been also cited as a random phoretic fungus even though the entomopathogenic potencial of this genus has also been reported [83,84], giving two plausible explanations of its presence in spore suspension.…”
Section: Discussionmentioning
confidence: 99%
“…Cladosposrium sp. has been also cited as a random phoretic fungus even though the entomopathogenic potencial of this genus has also been reported [83,84], giving two plausible explanations of its presence in spore suspension.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrosequencing (454) yielded many more bacterial sequences than DGGE, as has been found in other studies of bacteria associated with sap sucking insects. For example, studies using DGGE or restriction fragment length polymorphism (RFLP) identified only three and four bacterial symbionts in the sweetpotato whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) and Pentastiridius leporinus (Hemiptera: Cixiidae), respectively [5,19], compared to studies using 454 pyrosequencing describing 13 and 21 bacterial genera associated with the brown planthopper Nilaparvata lugens (Hemiptera: Delphacidae) [68] and the leafhopper Orosius albicinctus (Hemiptera: Cicadellidae), respectively [33].…”
Section: Discussionmentioning
confidence: 99%
“…Both are very common environmental fungi, including many plant commensals and pathogens [3,13]. A number of strains have also been isolated from insects, including some pathogenic ones [1,12,19]. More detailed work, including using finer-scale molecular markers, will be needed to determine whether these fungi are true mealybug associates or more transient environmental samples acquired via feeding [14].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors claim that Beauveria bassiana is a "species complex", referring that different isolates have a restricted host, while others point out that this fungus has no host specificity [29]. Accordingly, several pests are susceptible to the entomopathogenic aptitude of this fungus, like Alphitobius diaperinus [36], whiteflies Bemisia tabaci and Trialeurodes vaporariorum [32], Capnodis tenebrionis [20], Lutzomyia longipalpis [2], Callosobruchus maculates [26] and Tetranychus urticae [10]. Some studies also indicate the presence of this fungus associated to several lepidopterans [2,3,7,13,22,32,36].…”
Section: Fungal Ecological Rolesmentioning
confidence: 99%